Collection of Property Tax and Rural Municipal Fees in Peru - López Jiménez, Joselino (2026)
In this paper we have identified that in Latin America, as well as in Peru, there is a deficient municipal institutional capacity for municipal tax collection, but there are also coincidences in delinquency, lack of correct information to the taxpayer and the need to search for new collection strategies. The main objective is to identify and categorize successful strategies of municipal institutional capacity to improve the collection of property tax and municipal taxes. The study of 50 scientific articles selected from academic databases and specialized repositories, such as Scopus, Scielo, Web Of Science, was carried out. The inclusion of studies that provide quantitative and qualitative data on the effectiveness of interventions.   The study was developed under a qualitative approach, with a descriptive design based on a systematic review of relevant literature on successful strategies of municipal institutional capacity, and collection of property taxes and municipal taxes in Latin America. As a result, we have that the strengthening of municipal institutional capacity has proven to be fundamental to achieve and implement an effective, efficient and sustainable collection of property tax and municipal taxes, with respect to previous years, highlighting that some aspects such as: A cadastral update, tax diversification, staff training, improvement in administrative management, the adequate regulation of municipal taxes and duties, the creation of a tax culture, digital transformation of services and the use of real-time technologies, etc. They can have a direct impact on increasing tax revenues in local municipalities. It is concluded that the systematic review reveals that one of the successful strategies to increase property and municipal tax collection is the strengthening of municipal institutional capacity as long as it is accompanied by a comprehensive vision of governance, transparency, citizen participation, innovation and technical support.